2017
DOI: 10.3389/fphys.2017.00156
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of the Claudin Interactome in Malignant Pleural Mesothelioma: Evaluation of the Effect of Disease Phenotype, Asbestos Exposure, and CDKN2A Deletion Status

Abstract: Malignant pleural mesothelioma (MPM) is a highly aggressive tumor primarily associated with asbestos exposure. Early detection of MPM is restricted by the long latency period until clinical presentation, the ineffectiveness of imaging techniques in early stage detection and the lack of non-invasive biomarkers with high sensitivity and specificity. In this study we used transcriptome data mining in order to determine which CLAUDIN (CLDN) genes are differentially expressed in MPM as compared to controls. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…Although several reports suggested that the expression level of the CLDN15 transcript is elevated in MPM tissues 22 24 , 27 , to date there has been no report examining the protein expression of CLDN15 in MPMs. In this study, we showed that claudin-15 is the most abundantly expressed claudin in mesothelial tissues and demonstrated that CLDN15 protein is also detected at a high level in MPM tissues using newly established anti-human CLDN15 mAbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several reports suggested that the expression level of the CLDN15 transcript is elevated in MPM tissues 22 24 , 27 , to date there has been no report examining the protein expression of CLDN15 in MPMs. In this study, we showed that claudin-15 is the most abundantly expressed claudin in mesothelial tissues and demonstrated that CLDN15 protein is also detected at a high level in MPM tissues using newly established anti-human CLDN15 mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…It is also unknown which CLDN proteins are expressed in human malignant mesothelioma tissues. On the other hand, several lines of evidence indicate that the expression of CLDN15 mRNA is overexpressed in the epithelioid subtype of MPMs 21 24 , which accounts for approximately 60% of MPM cases 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Even though the functional role of many of these genes in MPM pathophysiology is yet to be confirmed, their differential expression could serve as a diagnostic, and therapeutic tool [ 23 ]. Remarkably, the expression ratio between the Claudin family gene CLDN15 , which is normally downregulated in cells undergoing EMT, and the VIM gene, a marker for the mesenchymal state, was a significant discriminating signature between subgroups [ 124 ]. Observations like these indicate that incorporating genetic mutation profiles with gene expression deregulations would enable the identification of actionable alterations and facilitate the development of targeted therapies.…”
Section: Genomics Of Malignant Pleural Mesotheliomamentioning
confidence: 99%
“…It has been suggested that in MPM patients with sarcomatoid histology, radical surgery should be excluded, and therapy should aim at symptom control and preservation of quality of life [36]. Considering the importance of clear histological subtype distinction in the initiation of the appropriate therapeutic intervention, it would be of great interest to investigate the transcriptional expression of the 30 significantly deregulated genes—identified in this study—with respect to the MPM phenotype [22]. Unfortunately, data relative to the histological subtype of MPM specimens were not available in the GDS1220 mesothelioma study.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we aimed at the identification of the differential expression of wound-healing-associated genes in MPM. For this purpose, we used established data mining techniques and transcriptomic analysis [19,20,21,22]. Moreover, we investigated their potential prognostic value as well as the functional enrichments of gene ontologies (GO) relative to the microRNAs (miRNAs) that regulate the significantly differentially expressed wound-healing-related genes in MPM.…”
Section: Introductionmentioning
confidence: 99%